Referencing geostrophic velocities using ADCP data at 24.5 degrees N (North Atlantic) - Comas-Rodriguez, Isis; Hernandez-Guerra, Alonso; Mcdonagh, Elaine L. (Scientia Marina, 2010)
Acoustic Doppler Current Profilers (ADCPs) have proven to be a useful oceanographic tool in the study of ocean dynamics. Data from D279, a transatlantic hydrographic cruise carried out in spring 2004 along 24.5°N, were processed, and lowered ADCP (LADCP) bottom track data were used to assess the choice of reference velocity for geostrophic calculations. The reference velocities from different combinations of ADCP data were compared to one another and a reference velocity was chosen based on the LADCP data. The barotropic tidal component was subtracted to provide a final reference velocity estimated by LADCP data. The results of the velocity fields are also shown. Further studies involving inverse solutions will include the reference velocity calculated here.